PENGGUNAAN APLIKASI CLOUDX DAN QUIZZIZ UNTUK MENDUKUNG PEMBELAJARAN SEJARAH SECARA DARING - Tiarima Marbun (Khazanah Pendidikan, 2022)
This remote classroom action research (CAR) was conducted to improve learning outcomes through CloudX, an application media. The subjects of this study were high school students, XII IPS-3 SMA Negeri 2 Tarakan. They are 33 students, consisting of 12 male students and 21 female students. It was  chosen since the students are solid and easy to cooperate. There are many problems in it, but the students are generally more responsive to the teacher. This classroom action research was conducted in two cycles with three teaching meetings in each. Both is designed to improve their learning outcomes using the CloudX. The results of the research prove that through the media can improve the students’ learning outcomes, as evidenced by the data in each aspect of observation. The action imlemented has been proved to have a good impact on the learning process. In the learning outcomes aspect, first cycle of meeting 1 showed 63.6% while in the second cycle of meeting 6 it increased to 90.9%% even though there were still 3 students or 9.1% had not achieved minimum completeness and 1 person was never present from the beginning research until the research is completed. Thus, the students who have not completed will be given remedial in a separate meeting in Google Classroom so as to achieve completeness in learning. Thus, learning using the CloudX has been proved to increase the student learning outcomes. It is recommended for teachers to use the CloudX Application in online learning.